The Hasat Bani Salt in the al-Zahirah Province of the Sultanate of Oman - Yule, Paul A. (2001)
The Hasat Bani Salt is South-eastern Arabia's largest and most important rock art monument. Often referred to as Coleman's Rock, it is named after the geologist who, by word of mouth, made it known in expatriate circles in the 1980s. An improvement of its documentation allows a better idea regarding its dating and meaning.
Keywords: Géologie -- Oman

مقابر منطقة سمد الشان ، مادة علمية لدراسة التاريخ الحضاري في سلطنة عمان - Yule, Paul A. (أدوماتو, 2001)
Keywords: Archéologie -- Oman

Sasanian Presence and Late Iron Age Samad in Central Oman, some Corrections - Yule, Paul A. (2008)
The question arises as to the nature of Parthian and Sasanian presence in south-eastern Arabia. Important is the role of the archaeological record in Oman in the early first millennium CE. The excavator has emended his chronology for late pre-Islamic Oman, de-emphasizing the evidence of radiocarbon dating. Recently in prominent places, Derek Kennet ignored and denigrated key results won from excavation and study in the 1990s. By means of the selective citing of sources, he concludes that the Samad cultural assemblage predates the first century CE.
Keywords: Archéologie -- Oman

Die Gräberfelder in Samad al Shan (Sultanat Oman): Materialien zu einer Kulturgeschichte - Yule, Paul A. (Orient-Archäologie, 2001)
Keywords: Archéologie -- Oman

كنز المعادن من سلمي / عبري في سلطنة عمان - Yule, Paul A. (أدوماتو, 2002)
Keywords: Archéologie -- Oman

Did the Ancient Mesopotamian Royal Stone Originate in Oman ? - Yule, Paul A. (أدوماتو, 2001)
Keywords: Archéologie -- Oman

Al-Fueda near Amla, Sultanate of Oman - Bank, Charlotte; Yule, Paul A. (Proceedings of the Seminar for Arabian Studies, 2001)
Keywords: Archéologie -- Oman